ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø¬Ø§Ù…Ø¹Ø© Ù…Ø§ØªØ§Ø±Ø§Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ù„Ù„Ø¹Ø§Ù… Ø§Ù„Ù…Ø¹Ù‡Ø¯ÙŠ 2021/2022 â€œLa Taskutâ€Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ - Fatia Rahmanita; Wirawan Jamhuri (Lughatu Ad-Dhat, 2023)
In ma'had al-Jami'ah there are many alumni of public schools who have never studied Arabic before, therefore ma'had al Jami'ah held a language program called